2019
DOI: 10.4103/jnrp.jnrp_183_18
|View full text |Cite
|
Sign up to set email alerts
|

Is Freehand Technique of Pedicle Screw Insertion in Thoracolumbar Spine Safe and Accurate? Assessment of 250 Screws

Abstract: Background: Pedicle screw fixation is one of the widely used procedures for instrumentation and stabilization of the thoracic and lumbar spine. It has the advantage of stabilizing all the three columns in single approach. Various assistive techniques are available to place the pedicle screws more accurately but at the expense of increased exposure to radiation, prolonged surgical duration, and cost. Objective: The objective of this study is to determine the accuracy and safety of pedicle screw fixation in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…However, compared to others, free-hand techniques are less expensive and less complex, with less radiation exposure to both patient and surgeon and less intraoperative time [ 8 ]. Moreover, based on previous researches, free-hand technique has an acceptable safety and accuracy [ 9 ]. We performed this study to answer five questions regarding the safety and the accuracy of free-hand technique during pedicle screw instrumentation.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared to others, free-hand techniques are less expensive and less complex, with less radiation exposure to both patient and surgeon and less intraoperative time [ 8 ]. Moreover, based on previous researches, free-hand technique has an acceptable safety and accuracy [ 9 ]. We performed this study to answer five questions regarding the safety and the accuracy of free-hand technique during pedicle screw instrumentation.…”
Section: Discussionmentioning
confidence: 99%
“…1,5 Freehand technique in an experienced surgeon simplifies the process of pedicle screw insertion and speeds up surgical procedure, and there is no risk of radiation exposure. 1,2,8 In a metaanalysis, Tian et al¹ investigated the accuracy of pedicle screw insertion in various spinal diseases with various methods and they found that navigated technique was more accurate along with similar clinical outcomes. AIS patients are mostly teenager and unnecessary radiation exposure during surgery need to be avoided for their good quality of life in the future.…”
Section: Ais=adolescent Idiopathic Scoliosismentioning
confidence: 99%
“…1,3,5 Malposition of a pedicle screw could violate the spinal cortex, causing neurological and vascular complications. 1,2 Owing to financial reasons, a lack of equipment, and radiation safety for medical personnel and patient, our institution adopted the freehand technique. The pedicle screw insertion of thoracic and lumbar spine in this technique is guided by anatomical marker only instead of fluoroscopy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These two surgical approaches use different methods for inserting pedicle screws. One is the traditional freehand technique ( Karapinar et al, 2008 ; Mattei et al, 2009 ; Vijayeswaran et al, 2019 ; He et al, 2022 ), and the other is the minimally invasive image-guided technique ( Gelalis et al, 2012 ; Lieberman et al, 2020 ; Sun et al, 2020 ; Li et al, 2022 ; Zhang et al, 2023 ). These two techniques also correspond to different pilot hole profiles.…”
Section: Introductionmentioning
confidence: 99%